APPLICATION OF A STOCHASTIC FRONTIER PRODUCTION FUNCTION FOR MEASUREMENT AND COMPARISION OF TECHNICAL EFFICIENCY OF MANDARIN FISH AND CLOWN FISH PRODUCTION IN LOWLANDS RESERVOIRS, PONDS AND DAMS OF CROSS RIVER STATE, NIGERIA - I. B.; Adinya; B. O. Offem; G. U. Ikpi (Journal of Animal and Plant Sciences, 2011)
This study compared technical efficiency of mandarin fish and clown fish production in Cross River State, Nigeria. Data were obtained from 240 respondents including 120 mandarin fish farmers and 120 clown fish farmers, which were randomly selected from villages in the study area by means of structured and semi-structured questionnaire. Data collected were analyzed using descriptive statistics and stochastic frontier function that incorporated inefficiency effects that were estimated using the Maximum Likelihood Estimate (MLE). The result showed that the sum of elasticity for mandarin fish and clown fish were found to be 1.36 and 1.25, respectively implies that both production systems were operated in inefficient stage (technically inefficient). The result also showed that fish farmers’ educational level, access to credit, farm size and feed positively influenced their levels of efficiency in mandarin fish and clown fish production systems in Cross River State. Extension agents should guide fish farmers on levels of inputs combination that would ensure efficient production of fish. Regular awareness campaign about new technologies in fish production should be embarked on by extension agents; this will enable fish farmers adopt new technologies in fish production. Extension agents should train fish farmers on improved production technique while banks should give loans to fish farmers and strictly monitor all her loan beneficiaries to ensure loan repayment. The study also recommends efficient policy formulation and implementation that will encourage fish farmers and unemployed youth in Cross River State to join fish producers cooperative(s) to enable them obtain loans at low interest rate from banks for increase in their capital base for higher output.
Keywords: Analysis; Efficiency; Fish; Production; Resource; Use.